Challenging Gender Binary: A Study of Shyam Selvadurai's the Funny Boy: Exploring Gender Non-Conformity and Cultural Tensions in Shyam Selvadurai's The Funny Boy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Shyam Selvadurai's novels give a vivid picture of the fears provoked by gender non- conformity and have the background of the battle of the spirit against the repression of gender, race, and sexual orientation. His protagonists find it challenging to accommodate their desires within the heteronormative structure of the family. Selvadurai's most acclaimed novel, The Funny Boy, focuses on coming-of-age of Arjie Chelvaratnam and follows his awakening as homosexual living in Sri Lanka. This novel is set against the backdrop of Sri Lankan social and cultural tensions in the 1980s. It explores the barriers around love, marriage, and cultural tensions, specifically in the Sinhalas and Tamils. Selvadurai's choice to place his narration in an unnamed center space in between established sexual and gender boundaries in several manners parallels the inability of diasporic individuals to be located within cultural and ethnic frontiers. This paper tends to explore the issue of being a gender non-conformist and of being different in a funny way. It highlights how the protagonist, through boundary transgressions and the destabilizing character of his subjectivity, challenges the fixity and finality of the socially constructed categories of gender.